THE CARAVAN HEALTH PROJECT ULBRA CARAZINHO AND ACTIONS OF THE PHYSICAL EDUCATION COURSE. (Fiep Bulletin - online, 2016)
It has intend to show in this work, the multidisciplinary enunciate teaching and health extension reach area of ULBRA Carazinho through Caravan Health Project ULBRA Carazinho, which is linked to the Specialization Course in Health Teaching (UFRGS), through new ways to rethink health practices, including SUS, it has teachers health like protagonist. Inaddition, it can adjust demands and services a new conception of innovative education. At first, the project was approved and registered by ULBRA extension, and it's characterized primarily for the direct assistance to community needs around, such as: lectures, circles conversations, health fairs and others actives and it was developed according to availability the time in the unit and prior scheduling our presence with the community with emphasis on education and coordination and exchanges teachers and students knowledge in health. The actions of project “Health Caravan ULBRA Carazinho” were diverse, so this moment, they included different cities. 13 extension actions were conducted in 6 small town with participation the 6 teachers and 158 students, this actions reached about 1113 people. In this way, we operate inseparable way to the theory and practice through qualification our education practices work; they have institutional in nature that does the difference in the health education in particular context with Physical Education.
Keywords: Education. Capacitation. Health. Project. Community Intervention